2003
DOI: 10.1016/s0929-1199(01)00036-0
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization of the firm: theory and evidence

Abstract: Jensen and Meckling (1992) hypothesize that the finn's decentralization decision is determined by a tradeoff of knowledge transfer costs and control (agency) costs. To maximize value, either knowledge must be transferred to those with the right to make decisions or decision rights must be transferred to those who have the knowledge. We identify characteristics of firms' investment opportunity sets that affect knowledge transfer and control costs and generate testable predictions about the relations between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(119 citation statements)
references
References 14 publications
3
100
0
9
Order By: Relevance
“…Nonetheless, the contributors of resources (the only principal taken into consideration) to non-profit organizations transfer decision rights to knowledge sources (in a process similar to for-profit firms), provided that transfer costsderived from the design of the incentive compensation program-do not exceed the benefits that arise from granting these rights [5], [24]. We thus expect that as delegation increases, managers will increasingly use incentive compensation, which is defined for our purposes as a mix of both intrinsic and extrinsic rewards.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the contributors of resources (the only principal taken into consideration) to non-profit organizations transfer decision rights to knowledge sources (in a process similar to for-profit firms), provided that transfer costsderived from the design of the incentive compensation program-do not exceed the benefits that arise from granting these rights [5], [24]. We thus expect that as delegation increases, managers will increasingly use incentive compensation, which is defined for our purposes as a mix of both intrinsic and extrinsic rewards.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…We define size as the number of present and prospective projects the organization has under funding or presented for funding, respectively, at the present time (PROJ). In other words, we use project number as a proxy for size in the same way that annual sales are used to capture the firm size of for-profit firms [24] 2 .…”
Section: Knowledge Of the Organizational Culture (Kcrit)mentioning
confidence: 99%
“…The private information effect refers to controlling shareholders managing inside information so as to avoid interventions by other shareholders (Jensen and Meckling ,1992;Christie, Joye, and Watts, 1993). Pyramidal structures and cross-share holdings can maximize the entrenchment and private information effects (Morck et al, 1998).…”
Section: Separation Of Governance and Ownership And The Relationship mentioning
confidence: 99%
“…For example, Boyd has suggested that the CEO duality-firm performance relationship depends on environmental dynamism and complexity [6]. With a high extent of environmental uncertainty, a high extent of decentralization may be less favored [8], and unified decision-making would be critical for success. Built on Boyd's work [6], recent evidence indeed documents a positive moderating effect of environmental uncertainty [29].…”
Section: Introductionmentioning
confidence: 99%